Examining "colour" as a ground of prohibited discrimination in international human rights law with specific reference to the "intra-racial" colourism against persons with albinism in the Democratic Republic of Congo (DRC) - Nienaber, A.G. (Annelize Gertruida) (University of Pretoria, 2023)
Dissertation (LLM (International Law))--University of Pretoria, 2022.